1995
DOI: 10.1042/bj3120979
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the active site of oligosaccharyltransferase from pig liver using synthetic tripeptides as tools

Abstract: Oligosaccharyltransferase (OST), an integral component of the endoplasmic-reticulum membrane, catalyses the transfer of dolichyl diphosphate-linked oligosaccharides to specific asparagine residues forming part of the Asn-Xaa-Thr/Ser sequence. We have studied the binding and catalytic properties of the enzyme from pig liver using peptide analogues derived from the acceptor peptide N-benzoyl-Asn-Gly-Thr-NHCH3 by replacing either asparagine or threonine with amino acids differing in size, stereochemistry, polarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 27 publications
(42 reference statements)
4
48
2
Order By: Relevance
“…When the Ser residue at position 163 is eliminated, the nearest C-terminal potential hydrogen acceptor is a threonine residue at position 167. It has previously been reported that N-glycosylation could still occur if the side-chain hydroxyl group on the Ser/Thr amino acid in the ϩ2 position was replaced with an amide (13). Although Trp residues have a nitrogen atom in the indole ring, the Trp residue at position 161 is an unlikely candidate as a hydrogen acceptor, because the electron pair of the indole nitrogen is delocalized and participates in the aromatic system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the Ser residue at position 163 is eliminated, the nearest C-terminal potential hydrogen acceptor is a threonine residue at position 167. It has previously been reported that N-glycosylation could still occur if the side-chain hydroxyl group on the Ser/Thr amino acid in the ϩ2 position was replaced with an amide (13). Although Trp residues have a nitrogen atom in the indole ring, the Trp residue at position 161 is an unlikely candidate as a hydrogen acceptor, because the electron pair of the indole nitrogen is delocalized and participates in the aromatic system.…”
Section: Discussionmentioning
confidence: 99%
“…It was subsequently determined, through the use of synthetic peptides containing Thr analogues in the ϩ2 position, that introduction of charge or movement of the side-chain methyl group was not tolerated by the OST complex (13,14). The outcomes of these studies suggest the presence of a hydrophobic binding pocket in the active site of the OST complex, which results in preferential glycosylation of NXT relative to NXS due to the presence of the side-chain methyl group of Thr (15).…”
Section: From the Department Of Process And Product Development Amgementioning
confidence: 99%
“…Replacing the acceptor Asn in the sequon by the corresponding primary amine results in the residue 2,4-diaminobutanoic acid (Dab), which was reported to have inhibitory effects on eukaryotic OST 14,24 . We determined a K d of 10±0.25 mM for a synthetic peptide containing Dab at the acceptor position (Table 1, compound 9, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies involving mutation of the ϩ2 amino acid following the Asn residue have shown that a hydrogen acceptor is necessary to render the Asn residue sufficiently nucleophilic to displace the GlcNAc 2 Man 9 Glc 3 oligosaccharide from the dolichol donor (3,4). Further insight into the mechanism of N-glycosylation was obtained by replacing the ϩ2 amino acid in the consensus sequon with threonine analogues (5,6). The results from these studies indicated that the OST enzyme complex did not tolerate changes in the position of the threonine methyl group nor the introduction of charge at the ϩ2 residue.…”
mentioning
confidence: 99%